Application of renewable energy for a rural village in Thailand energy survey and data assessment - Ora Rojanastien; Follea, D.; Pakorn Adulbhan; Ir. Walter, Despiegelaere; Self Support (Bangkok : Asian Institute of Technology, 1981)
In order to find the most appropriate energy system for a group of households, or a village, the perceived needs of the villagers, energy demand during the day and during the year of each household, the information about available energy resources, and socio-economic and environmental information of the group of households must be found. The energy survey of the group of households in village w- 12 of Tarobol Bang Pla, Bang Phli District, Samut Prakarn Province, was conducted in order to construct an effective methodology for conducting an energy survey of other villages, and in order to provide sufficient information for the technical matching process, for Cost-Benefit analysis, and for social and environmental matching process of the project of finding the most appropriate energy system for the rural village in Thailand. Although the questionnaire was designed for use in conducting the survey of this group of households, it can also be used for energy survey of other villages with a little bit modification. The following information was obtained from the survey:- 1) The villagers want to change the way of pumping the water into, or out of, the fish-pond. 2) The characteristics of the energy consumption of the group of households which are in the forms of seasonal and diurnal variation of the energy consumption in each activity, the proportion of energy used in each activity, and the proportion of energy provided by each type of fuel used in each activity. It has been found that fish-pond water pumping consumes more energy than other activities, and this activity consumes 1864 GJ of energy from diesel oil. 3) Only three kinds of renewables energy resources are available; solar and wind energy resources, and biomass -resources. The availability of these energy resources with respect to space and time was found. 4) The average income per year of each household is about 700,00 Baht with the standard deviation of 50,000 Baht. The average educational level of the villagers is the primary school.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1981
Keywords: Renewable energy sources -- Data processing